Enhanced negative magnetoresistance near the charge neutral point in Cr doped topological insulator. Issue 23 (14th April 2021) - Guo, Qixun; Wu, Yu; Wang, Dongwei; Han, Gang; Wang, Xuemin; Fu, Libo; Wang, Lihua; He, Wei; Zhu, Tao; Zhu, Zhendong; Liu, Tao; Yu, Guanghua; et al.
Abstract : Negative magnetoresistance (MR) is not only of great fundamental interest for condensed matter physics and materials science, but also important for practical applications, especially magnetic data storage and sensors. Abstract : Negative magnetoresistance (MR) is not only of great fundamental interest for condensed matter physics and materials science, but also important for practical applications, especially magnetic data storage and sensors. However, the microscopic origin of negative MR is still elusive and the nature of the negative MR in magnetic topological insulators has still not been completely elucidated. Here, we report magnetotransport studies on Cr doped (Bi1− x Sb x )2 Te3 topological insulator thin films grown by magnetron sputtering. At the temperature of 2 K, a giant negative MR reaching 61% is observed at H = 2 T. We show that the negative MR is closely related to the position of the Fermi level, and it reaches the maximum when the Fermi level is gated near the charge neutral point. We attribute these results to the Coulomb potential due to the random composition fluctuations in Cr doped (Bi1− x Sb x )2 Te3 . Our results provide a deeper insight into the mechanism of negative MR, and are helpful to realize the quantum anomalous Hall effect in the sputtered Cr-(Bi1− x Sb x )2 Te3 thin-film systems by tuning the Fermi level and reducing disorder effects.